2011
DOI: 10.7150/ijbs.7.715
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Morus alba Leaves Extract on Ocular Functions of Pups from Diabetic and Hypercholesterolemic Mother Rats

Abstract: Phytotherapy is frequently considered to be less toxic and free from side effects than synthetic drugs. Hence, the present study was designed to investigate the protective use of crude water extract of Morus alba leaves on ocular functions including cataractogenesis, biochemical diabetic and hypercholesterolemic markers, retinal neurotransmitters and retinopathy of rat pups maternally subjected to either diabetes and/or hypercholesterolemia. Application of crude water extract of Morus alba resulted in ameliora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 46 publications
7
39
0
1
Order By: Relevance
“…Similar findings of deformities of epiphyseal cartilage was reported by El-Sayyad et al (2010& 2015 who found reduction in long bone ossification and retarded differentiation of chondrification and osteoblast differentiation in rat foetus maternally fed on hypercholesterolemic diet.…”
Section: Discussionsupporting
confidence: 75%
“…Similar findings of deformities of epiphyseal cartilage was reported by El-Sayyad et al (2010& 2015 who found reduction in long bone ossification and retarded differentiation of chondrification and osteoblast differentiation in rat foetus maternally fed on hypercholesterolemic diet.…”
Section: Discussionsupporting
confidence: 75%
“…Blood glucose and insulin levels are also important for preventing oxidative stress in intravascular endothelial cells, and atherosclerosis. LEM has demonstrated a suppressive effect on atherosclerotic lesions in mice [7] and the protective effect on vascular system through the decreasing of oxidative stress and anti-glycation [18][19][20], suggesting that it should form part of the dietary therapy for type 1 and 2 diabetes mellitus, and for other metabolic syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…LEM does not directly stimulate insulin secretion, and suppress the glucose elevation. Furthermore, it improves anti-oxidative and anti-glycation activities in streptozotocin-induced chronic diabetic rat [18], also has the protective effects on vascular system in rats fed atherogenic diet [19], and on ocular functions in pups from diabetic mother rat [20]. So, the combinational use of SU-treatment and LEM is associated with the protection of systemic oxidative stress.…”
Section: Introductionmentioning
confidence: 97%
“…Sainfoin which contains rich condensed tannins can increase beneficial fatty acids and reduce skatole content in lamb meat [7] . Flavonoids from mulberry leaves (FML) have positive effects on the hypoglycaemic, antihypercholesterolemic and anti-oxidative potential in rats [8] .…”
Section: Introductionmentioning
confidence: 99%